Assessment of tolerance and acceptability between mannitol solution and polyethylene glycol as bowel preparation for colonoscopy: a three-center study - Piñerúa-Gonsálvez, Jean Félix (2020)
Introduction: Adequate bowel preparation is one of the most important factors related to the yield of colonoscopy. Low-quality bowel preparation has been associated with lower adenoma detection rates and increased healthcare expenses. Bowel preparation is a major impediment to undergo colonoscopy since it is perceived as an unpleasant experience by patients. Objective: This study was aimed to assess tolerance and acceptability of the bowel preparation using either polyethylene glycol (PEG) or mannitol solution. Materials and methods: We enrolled 140 patients with indications of screening for colorectal cancer or with suspected large bowel diseases. They received either mannitol solution or PEG as bowel preparation. Patients were asked to fill a questionnaire about the bowel preparation experience. Results: Patients perceived more burdensome the preparation with PEG than mannitol for the variables nausea overall experience, post-procedure discomfort, disagreeable flavor, volume ingested and cost (p<0.05). A similar tolerance was reported for abdominal pain, bloating and anal irritation (p>0.05). The acceptability was 82.9% and 71.4% in the Mannitol group and in the PEG group, respectively (p=0.10). Conclusion: Acceptance of the bowel preparation between mannitol solution and PEG was comparable. However, mannitol was bettertolerated by the patients in regard to most of the evaluated items.